Types of Partner Violence in Couples Affected by Incarceration: Applying Johnson's Typology to Understand the Couple-level Context for Violence. Issue 9 (May 2022) - McKay, Tasseli; Tueller, Stephen; Landwehr, Justin; Johnson, Michael P.
In prior research, samples of incarcerated and reentering men and their partners report partner violence at roughly 10 times the frequency found in the general population. The relationship dynamics underlying these experiences remain poorly understood. Addressing this gap and expanding prior applications of Johnson's typology in other populations—which typically rely on survey data alone and include reports from just one member of a couple—we applied latent class analysis with dyadic survey data from 1, 112 couples to identify types of partner violence in couples affected by incarceration. We assessed congruence between quantitative types and couples' qualitative accounts and compared the two major types using two-sample t -tests. In some couples, one partner used various tactics to systematically dominate and control the other, as in Johnson's coercive controlling violence. In others, physical violence arose in the context of jealousy but no other controlling behavior. This type resembled Johnson's situational couple violence. Qualitative data suggested that jealousy represented a common, situational response to periods of prolonged separation, relationship instability, status insecurity, and partnership concurrence and not a tactic of control per se. Victims of coercive controlling violence experienced more PTSD symptoms and felt less safe in their relationships than victims of jealous-only violence. Perpetrators of coercive controlling violence were more likely to use severe physical violence against their partners than perpetrators of jealous-only violence. Findings indicate that broader context is critical for interpreting the presence of jealousy (and whether it constitutes a control tactic). They indicate that prevention and response strategies tailored to these types could help couples cope safely with the extreme relationship stressors of incarceration and reentry. Finally, they suggest a need to move from an exclusive focus on individual accountability and services toward a model that also incorporates institutional accountability and change.